Coculture of Chondrocytes and Stem Cells: A Review of Head and Neck Cell Lines for Cartilage Regeneration - Lee, Michael Fook-Ho; Steffens, Daniel; Chung, Johnson H Y; Posniak, Steven; Cheng, Kai; Clark, Jonathan; Wallace, Gordon; Mukherjee, Payal (Cells, tissues, organs, 2025)
Bioprinting, using "bio-inks" consisting of living cells, supporting structures, and biological motifs to create customized constructs, is an emerging technique that aims to overcome the challenges of cartilaginous reconstruction of head and neck structures. Several living cell lines and culturing methods have been explored as bio-inks with varying efficacy. Coculture of primary chondrocytes and stem cells (SCs) is one technique well established for degenerative joint disease treatment, with potential for use in expanding chondrocyte populations for bio-inks. This study aimed to evaluate the techniques for coculture of primary chondrocytes and SCs for head and neck cartilage regeneration. A literature review was performed through OVID/Web of Science/MEDLINE/BIOSIS Previews/Embase. Studies reporting on chondrocytes and SCs in conjunction with coculture or cartilage regeneration were included. Studies not reporting on findings from chondrocytes/SCs of the head and neck were excluded. Extracted data included cell sources, coculture ratios, and histological, biochemical, and clinical outcomes. Fifteen studies met inclusion criteria. Auricular cartilage was the most common chondrocyte source (n = 10), then nasal septum (n = 5), articular (n = 1), and tracheal cartilage (n = 1). Bone marrow was the most common SC source (n = 9) then adipose tissue (n = 7). Techniques varied, with coculture ratios ranging from 1:1 to 1:10. All studies reported coculture to be superior to SC monoculture by all outcomes. Most studies reported superiority or equivalence of coculture to chondrocyte monoculture by all outcomes. When comparing clinical outcomes, coculture constructs were equivalent to chondrocyte monoculture in diameter and equivalent or inferior in wet weight and height. Coculture of primary chondrocytes and SCs is a promising technique for expanding chondrocyte populations, with at least equivalence to chondrocyte monoculture and superior to SC monoculture when seeded at the same chondrocyte densities. However, there remains a lack of consensus regarding the optimal cell sources and coculture ratios.